Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's solve the quadratic equation [tex]\( 2x^2 + 5x - 3 = 0 \)[/tex].
### Step-by-Step Solution
1. Identify the coefficients:
For a quadratic equation in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex], identify the coefficients [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex].
- Here, [tex]\( a = 2 \)[/tex],
- [tex]\( b = 5 \)[/tex],
- [tex]\( c = -3 \)[/tex].
2. Use the quadratic formula:
The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
3. Calculate the discriminant:
The discriminant [tex]\(\Delta\)[/tex] is:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values of [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ \Delta = 5^2 - 4 \cdot 2 \cdot (-3) \][/tex]
[tex]\[ \Delta = 25 + 24 \][/tex]
[tex]\[ \Delta = 49 \][/tex]
4. Compute the square root of the discriminant:
[tex]\[ \sqrt{\Delta} = \sqrt{49} = 7 \][/tex]
5. Substitute back into the quadratic formula:
[tex]\[ x = \frac{-5 \pm 7}{2 \cdot 2} \][/tex]
Simplify the two cases separately (using [tex]\(+\)[/tex] and [tex]\(-\)[/tex]).
Case 1 (Using +):
[tex]\[ x = \frac{-5 + 7}{4} \][/tex]
[tex]\[ x = \frac{2}{4} \][/tex]
[tex]\[ x = \frac{1}{2} \][/tex]
Case 2 (Using -):
[tex]\[ x = \frac{-5 - 7}{4} \][/tex]
[tex]\[ x = \frac{-12}{4} \][/tex]
[tex]\[ x = -3 \][/tex]
### Final Solution
The solutions to the quadratic equation [tex]\( 2x^2 + 5x - 3 = 0 \)[/tex] are:
[tex]\[ x = -3 \quad \text{and} \quad x = \frac{1}{2} \][/tex]
### Step-by-Step Solution
1. Identify the coefficients:
For a quadratic equation in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex], identify the coefficients [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex].
- Here, [tex]\( a = 2 \)[/tex],
- [tex]\( b = 5 \)[/tex],
- [tex]\( c = -3 \)[/tex].
2. Use the quadratic formula:
The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
3. Calculate the discriminant:
The discriminant [tex]\(\Delta\)[/tex] is:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values of [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ \Delta = 5^2 - 4 \cdot 2 \cdot (-3) \][/tex]
[tex]\[ \Delta = 25 + 24 \][/tex]
[tex]\[ \Delta = 49 \][/tex]
4. Compute the square root of the discriminant:
[tex]\[ \sqrt{\Delta} = \sqrt{49} = 7 \][/tex]
5. Substitute back into the quadratic formula:
[tex]\[ x = \frac{-5 \pm 7}{2 \cdot 2} \][/tex]
Simplify the two cases separately (using [tex]\(+\)[/tex] and [tex]\(-\)[/tex]).
Case 1 (Using +):
[tex]\[ x = \frac{-5 + 7}{4} \][/tex]
[tex]\[ x = \frac{2}{4} \][/tex]
[tex]\[ x = \frac{1}{2} \][/tex]
Case 2 (Using -):
[tex]\[ x = \frac{-5 - 7}{4} \][/tex]
[tex]\[ x = \frac{-12}{4} \][/tex]
[tex]\[ x = -3 \][/tex]
### Final Solution
The solutions to the quadratic equation [tex]\( 2x^2 + 5x - 3 = 0 \)[/tex] are:
[tex]\[ x = -3 \quad \text{and} \quad x = \frac{1}{2} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.